A citizen science approach for enhancing public understanding of air pollution. (January 2020) - Mahajan, Sachit; Kumar, Prashant; Pinto, Janaina Antonino; Riccetti, Agnese; Schaaf, Katinka; Camprodon, Guillem; Smári, Viktor; Passani, Antonella; Forino, Giuseppe
Highlights: A multi-component citizen science approach is designed for community engagement. Our approach revolves around the ideas of inclusion, collaboration and reciprocation. Behavioural changes can be promoted using tools like interactive air quality quiz. Citizen science workshops can result in establishing community-led air sensing schemes. Citizen scientists permit detection of events with wider spatial and temporal coverage. Abstract: The deterioration in air quality is a challenging problem worldwide. There is a need to raise awareness among the people and support informed decision making. Over the years, citizen science activities have been implemented for environmental monitoring and raising awareness but most of such works are contributory in nature, i.e. task design, planning and analysis are performed by professional researchers and citizens act as participants. Our objective is to demonstrate that citizen science can be used as a 'tool' to enhance public understanding of air pollution by engaging communities and local stakeholders. We present a co-creation based citizen science approach which incorporates the ideas of inclusion, where citizens are involved in most of the steps of the scientific process; collaboration, where the citizen scientists define research problems and methodologies, and reciprocation, where citizen scientists share their observations through storytelling. We integrate the use of interactive air quality quizzes, offline questionnaires and low-cost air quality monitoring sensors. The results show that such methods can generate insightful data which can assist in understanding people's perception and exposure levels at a fine-grained level. It was also observed that community engagement in air quality monitoring can enhance partnerships between the community and research fraternity.